FAKTOR-FAKTOR YANG MEMPENGARUHI HARGA SAHAM DI PERUSAHAAN PERBANKAN YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2018 – 2020 - Mitha Christina Ginting; Lamria Sagala (Sekolah Tinggi Ilmu Ekonomi-LMII Medan, 2021)
This study aims to examine and analyze the effect of the variables Return on Investment, Earning Per share, Price to Book Value, Inflation and Exchange Rate on Stock Prices in banking companies listed on the Indonesia Stock Exchange. The population of this study is 39 companies, by accessing financial statements and auditor reports through the Indonesia Stock Exchange website. The sampling method used is the Purposive Sampling method, so that 20 companies are obtained as samples for X 3 years of observation (2018-2020 period) with a total of 60 observations of analytical data. The data analysis method used is the analytical regression method. Based on the results of data processing using logistic regression method with SPSS 20 software, it is found that Return on Investment, Earning Per share, Price to Book Value, Inflation and Exchange Rate can simultaneously affect stock prices by 68%, the remaining 32%. Partially, Return on Investment, Earning Per share, Price to Book Value, and Exchange Rate have a significant effect on stock prices. However, Inflation has no significant effect on stock prices.